2014
DOI: 10.1111/fare.12070
|View full text |Cite
|
Sign up to set email alerts
|

Romantic Partner and Biological Father Support: Associations with Maternal Distress in Low‐Income Mexican‐Origin Families

Abstract: Paternal support is often linked to lower levels of maternal psychological distress; however, research has seldom considered the increasing numbers of Mexican‐origin families with a romantic partner social (RPS) father (i.e., mothers' partners who are not formally identified as stepfathers). This study applied a bioecological systems framework to test linkages between support from RPS fathers and maternal depressive symptoms and parenting stress and to consider whether nonresident biological father support and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Of note, emotional support has been demonstrated to have a greater impact on maternal stress than instrumental or financial support (Manuel, Martinson, Bledsoe-Mansori, & Bellamy, 2012; Ryan, Tolani, & Brooks-Gunn, 2009). The benefit of partner support is also not limited to the child’s biological father, as decreased maternal depression is associated with emotional support from other romantic partners as well (Gonzalez & Barnett, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, emotional support has been demonstrated to have a greater impact on maternal stress than instrumental or financial support (Manuel, Martinson, Bledsoe-Mansori, & Bellamy, 2012; Ryan, Tolani, & Brooks-Gunn, 2009). The benefit of partner support is also not limited to the child’s biological father, as decreased maternal depression is associated with emotional support from other romantic partners as well (Gonzalez & Barnett, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Maume () hypothesized that working‐class men were more likely to be employed in part‐time jobs and night shifts, which allowed them to do more kin work. Researchers have also documented that non‐Hispanic, Black fathers report more cooperation with relatives, but also more conflict with coparents' kin than non‐Hispanic Whites (Fagan, Levine, Kaufman & Hammar, ; Gonzalez & Barnett, ). Qualitative and ethnographic research provide insight into why these differences exist.…”
Section: Unpaid Work and Familiesmentioning
confidence: 99%
“…not formally identified as stepfathers (e.g., among Mexican-origin mothers with 3-year-old children; [46]), and the contributions of the quality of the marital relationship (e.g., the extent of agreement between partners on a range of family-related issues) to maternal well-being among mothers of children with developmental disabilities [47]. Similar to the findings of the present study, maternal distress and parenting stress are often interrelated [48][49][50], whereas evidence supporting a direct link of paternal involvement/support and perceptions of parenting/parental stress is less robust [45,46]. We drew from the existing literature in relatively comparable populations, and our data indicated that a composite assessing food and human insecurity and household crowding index, was a valid proxy to assess a mother's ability to meet her/her family's basic needs.…”
Section: Plos Onementioning
confidence: 99%